Particularities of Formation of Architectural Typology of Small Hotels in the South of Russia - BADAVI, Anna A.; MOLCHANOV, Victor M. (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
In Russia, since the 2000s the growth of tourists has begun to increase. This necessitates the building of different kinds of hotels. Minimal investment, territory and the need for staff allowed small hotels to occupy a large segment of the Russian hotel market. Based on this, we formed the problem of research – the lack of modern architectural typology of small hotels. The purpose of the article is to identify the features of the architectural typology of small hotels in the South of Russia. As one of the main factors constraining the development of tourism in Rostov Region, most researchers point to the absence of a sufficient number of accommodation facilities that meet modern requirements of comfort and adapted to the operational characteristics of each type of tourism. In the world of projecting and regulatory documents, there are 17 main types of small hotels which are considered in this research. Comprehensive research of the tourism sector in Rostov Region revealed the statistics of accommodation of tourists visiting the Rostov region. In the course of the research, the most common types of small hotels in Rostov Region were identified.